Challenging academic presentations - Milka Hadjikoteva (English Studies at NBU, 2015)
Academic presentations are hard to teach and students frequently have difficulties in their preparation and delivery. This article aims to present some of the findings of researchers in this area related to communication apprehension encountered both by native and non-native speakers of English. It also discusses the notion of high- and low-context cultures as well as various types of organization of presentations and overviews presentations as a process rather than a product developed with New Bulgarian University (NBU) students of EFL courses at level B1-B2 according to CEFR.